Global Impact of Ergot Alkaloids - Klotz, James L. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
"The Global Impact of Ergot Alkaloids" addresses the very broad topic of ergot alkaloids and the influence that they have on many facets of life. The content in this Special Issue pertains to research studying fungi, plants, livestock, and humans. While the perspectives of each paper may differ, the common aspect is the interest and emphasis on ergot alkaloids. These compounds cross the spectrum from feared toxins to potential pharmaceutical discoveries. The research included spans the globe and has content that will attract the interest of readers from many different backgrounds.